2022
DOI: 10.1245/s10434-022-11463-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Prognostic Factors for Early Recurrence in Intrahepatic Cholangiocarcinoma After Curative-Intent Resection

Abstract: Background. Recurrence rates of intrahepatic cholangiocarcinoma (iCCA) after curative hepatectomy are as high as 50% to 70%, and about half of these recurrences occur within 2 years. This systematic review aims to define prognostic factors (PFs) for early recurrence (ER, within 24 months) and 24-month disease-free survival (DFS) after curative-intent iCCA resections. Methods. Systematic searching was performed from database inception to 14 January 2021. Duplicate independent review and data extraction were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In general, the presence of regional LNM often portends a poor prognosis. 12 , 26 , 27 , 28 A growing number of studies have shown that the number of metastatic LNs has an impact on prognosis in many cancers. 29 , 30 However, there remains insufficient data regarding their association in ICC.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the presence of regional LNM often portends a poor prognosis. 12 , 26 , 27 , 28 A growing number of studies have shown that the number of metastatic LNs has an impact on prognosis in many cancers. 29 , 30 However, there remains insufficient data regarding their association in ICC.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis by Choi et al the authors identified four series describing early intrahepatic recurrence (defined as either 6, 12, or 24 months after resection) and noted a 49.6% 24-month intrahepatic recurrence rate, similar to our finding of 41%. 18 Unfortunately, the majority of patients will expereince liver recurrence, with most reports describing >50% isolated liver or simultaneous liver and extrahepatic Note: Data are n (%) unless noted.…”
Section: Discussionmentioning
confidence: 99%
“…This research also identified the role of multiple tumors and lymphatic metastasis in the prediction of EP, in line with a recently published systematic review. 31 An increase in the number of tumors and the presence of lymphatic metastasis indicates higher tumor burden in a more advanced stage, representing an essential prognostic factor for poor survival of ICC. 22 Besides, EP was more common in ICCs with ill-defined margin and APE.…”
Section: Discussionmentioning
confidence: 99%